Graphene-Based Organic Semiconductor Film for Highly Selective Photocatalytic CO2 Reduction - Yanghong Xu; Haopeng Tang; Yifei Wang; Xiaofeng Zhu; Long Yang (Nanomaterials)
Mimicking artificial photosynthesis utilizing solar energy for the production of high-value chemicals is a sustainable strategy to tackle the fossil fuel-based energy crisis and mitigate the greenhouse effect. In this study, we developed a two-dimensional (2D) graphene oxide (GO)–diketopyrrolopyrrole (DPP) film photocatalyst. GO nanosheets facilitate the uniform dispersion of DPP nanoparticles (~5 nm) while simultaneously constructing an efficient charge transport network to mitigate carrier recombination. Under visible-light irradiation in an aqueous solution without sacrificial agents, the optimized GO–DPP50 film catalyst exhibited exceptional performance, achieving a CO production rate of 32.62 μmol·g⁻1·h⁻1 with nearly 100% selectivity. This represents 2.77-fold and 3.28-fold enhancements over pristine GO (8.65 μmol·g−1·h−1) and bare DPP (7.62 μmol·g−1·h−1), respectively. Mechanistic analysis reveals a synergistic mechanism. The 2D GO framework not only serves as a high-surface-area substrate for DPP anchoring, but also substantially suppresses charge recombination through rapid electron transport channels. Concurrently, the uniformly distributed DPP nanoparticles improve visible-light absorption efficiency and facilitate effective photogenerated carrier excitation. This work establishes a novel paradigm for the synergistic integration of 2D nanomaterials with organic semiconductors, providing critical design principles for developing high-performance film-based photocatalysts and selectivity control in CO2 reduction applications.